Zmiany strategiczne w kształtowaniu innowacyjności przedsiębiorstwa - Pomykalski, Przemysław (Strategic Changes in Shaping of an Innovative Company, 2008)
Innovation is one of the most important sources of competitive advantage. Value creation is the primary target, however, it allows for a small degree of flexibility in designing the strategy. Companies should use simplified financial metrics in their decision making process to ensure flexibility in their strategy that allows for faster market response and even proactive ventures.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 309-318